Notes on some species of Naarda Walker, 1866 from Australia and Wallacea (Lepidoptera: Erebidae, Hypeninae) - Tóth, Balázs (Zootaxa, 2026)
The genitalia of Naarda xanthonephra Turner, 1908 and N. calliceros Turner, 1932 are illustrated and described for the first time. Lectotypes are designated for N. coelopis Turner, 1936 and N. calliceros Turner, 1932. The synonymy of N. xanthonephra and N. coelopis Turner, 1936 is confirmed. Two new species, N. inopina sp. nov. from the Banda Islands and N. turneri sp. nov. from Australia, are described, increasing the number of known species of the genus Naarda recorded from the Australian continent to three. The paper is accompanied by 15 figures illustrating the examined taxa and diagnostic characters.